DEM analysis of shear mechanical characteristics for rock fractures with a same roughness index θ* max /(C + 1) - Jiuyang Huan; Mingming He; Hengfei Pan; Weijia Yu; Chen Ge; Weitao Huan; Mengdie Hu (European Journal of Environmental and Civil Engineering, 2026)

Competitive adsorption of benzohydroxamic acid and butyl xanthate onto amorphous Ti(OH)4: Kinetics, selectivity and surface coordination - Xiulin Wang; Jingzhong Kuang; Qinglong Liu; Lufeng Zeng; Mingming Yu; Lingguo Meng (Minerals Engineering, 2026)

State-dependent alterations of network characteristics between seizure and non-seizure onset zones in drug-resistant epilepsy - Kunlin Guo; Kunying Meng; Renping Yu; Lipeng Zhang; Yuxia Hu; Rui Zhang; Dezhong Yao; Mingming Chen (Cognitive Neurodynamics, 2026)

Genomic identification, pangenome analysis, and antimicrobial resistance of Aeromonas spp. isolated from food and foodborne outbreaks - Mingming Yu; Yimeng Wang; Lidan Jiang; Dehui Liu; Bin Hu; Xuting Yang (International Journal of Food Microbiology, 2026)

Ti3C2Tx-polypyrrole composite hydrogel with hierarchical mass transfer channels for efficient salt-tolerant solar evaporation - Cheng Chen; Cunxiu Zhang; Shengyi Wang; Wanneng Yu; Yuxiu Dong; Yuezi Huang; Mingming Guo (Desalination, 2026)

Tannic acid-crosslinked zein–lipase complex stabilized multichamber Pickering emulsion for efficient diacylglycerol production - Zhouliang Sun; Yufei Zhang; Ji Zhang; Yi Zhang; Huanyu Zheng; Yang Li; Chen Yu; Mingming Zheng (Food Chemistry, 2026)

Unlocking soil food webs for pollution remediation: A cross-trophic systems perspective - Linhui Jiang; Nan Jin; Yue Pan; Dingyu Shen; Ziyang Wang; Zhihua Yin; Mingming Sun; Lei Yu; Shui Wang (Soil Ecology Letters, 2026)

A robust HPLC-HILIC enrichment system for O-glycoproteomics profiling of plasma and cerebrospinal fluid across Alzheimer's disease progression - Zhenpeng Deng; Yan Wang; Lei Liu; Xin Guo; Haiyang Zhu; Mingming Dong; Yusong Ge; Yongliang Yu; Mingliang Ye (Analytica Chimica Acta, 2026)

Unraveling the co-evolution of lipidome and flavorome during the light-frying of grass carp cubes: Interactions between lipid oxidation and Maillard reaction - Jinlin Li; Xinwu Hu; Shuanglong Wang; Li Huang; Hanhao Zhou; Chengwei Yu; Mingming Hu; Zongcai Tu; Bizhen Zhong; Bin Peng (Food Chemistry, 2026)

RGI-Net: A Recursive Gated Injection Network for Underwater Image Restoration in Marine Inspection - Yu Lin; Mingming Wen; Shuiyuan He; Laiyong Song (Journal of Marine Science and Engineering, 2026)
Background: Underwater optical imagery used in marine inspection is degraded by wavelength-dependent attenuation and scattering, which couple color cast with structural haze. Existing restorers either treat both degradations in one stage or cascade separate networks and exchange information only through reconstructed images. Methods: This paper proposes RGI-Net, combining (i) a shared-weight two-pass pipeline that disentangles Lab chromatic correction from RGB structure refinement without duplicating the backbone and (ii) a 1×1 Gated Injection Bridge that transfers Pass-1 bottleneck features into Pass 2 under a learned element-wise gate, together with a recursive contrastive objective that includes a cross-pass consistency term. All methods are compared on identical test partitions under one evaluation pipeline (UIEB train/test, LSUI, EUVP, U45, C60). Results: Against WaterNet, PUIE-Net, CCL-Net, and Phaseformer, RGI-Net attains the best UIEB UIQM (2.21) and UCIQE (0.372), with PSNR/SSIM statistically indistinguishable from Phaseformer (Wilcoxon p>0.5). On the reported GPU, wall-clock latency is 41.00 ms, versus 61.64 ms for Phaseformer at 256×256, while RGI-Net has the largest parameter count and FLOPs in the comparison. Conclusions: Shared two-pass decoupling with gated bottleneck injection improves UIEB no-reference indices. Lower latency than Phaseformer on one workstation GPU is not a claim of overall computational efficiency, given the larger parameter and FLOP counts. UIQM and UCIQE are operational scores, not perceptual or inspection-task evidence; on EUVP, the best UIQM/UCIQE coincide with the lowest PSNR/SSIM among compared methods, which remains a substantial limitation.

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Asymmetric atmospheric secondary circulation response to a sea surface submesoscale cold filament - Jun Yang; Ziqi Zhang; Jen-Ping Peng; Dongxiao Wang; Chunhua Qiu; Rui Shi; Mingming Shao; Shichang Zhao; Fei Yu; Yihua Luan (Science China Earth Sciences, 2026)

Targeting Peroxiredoxin 6: Tannic Acid Inhibits Singapore Grouper Iridovirus Infection via PRDX6‐Dependent Pathway and Antioxidant Response - Xiangmou Qin; Chen‐Ao Li; Lin Huang; Qing Yu; Mingming Zhao; Yanxia Gao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; Junxiang Lai; Ermeng Yu; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a major viral pathogen threatening grouper aquaculture. The lack of specific antiviral drugs underscores the urgent need to develop safe and effective control strategies. This study demonstrates that tannic acid (TA) exhibits significant anti‐SGIV activity in vitro. In grouper spleen (GS) cells, TA inhibited SGIV replication in a concentration‐dependent manner. Time‐of‐addition assays confirmed its antiviral efficacy when applied either before or after SGIV infection. Mechanistically, TA directly interfered with SGIV particle infectivity, viral adsorption, entry and intracellular replication. Network pharmacology analysis suggested TA's targets are associated with host cellular antioxidant pathways, among which Peroxiredoxin 6 (PRDX6) was identified as a potential target of TA. Further experiments confirmed that TA upregulated the Nrf2 antioxidant pathway and suppressed the expression of pro‐inflammatory cytokines (IL‐1β, IL‐8). Notably, TA enhanced the expression of PRDX6, and overexpression of PRDX6 significantly inhibited SGIV replication, indicating that PRDX6 contributes to the antiviral effect of TA. In vivo, TA treatment not only restored PRDX6 expression in infected groupers but also significantly reduced viral load in liver and spleen following SGIV infection. These findings demonstrate that TA inhibits SGIV through direct viral interference and PRDX6‐mediated antioxidant modulation, highlighting its potential as a natural therapeutic agent against SGIV.

Measuring the impact of urban morphology on residential energy consumption at the neighborhood-level in the Netherlands - Han Yu; Mingming Hu; Arnold Tukker; Peter Berrill (Sustainable Cities and Society, 2026)

Ship-PFTracker: A robust ship tracking framework in short-time SAR imagery with particle filtering - Shanwei Liu; Ruikai Yu; Muhammad Yasir; Manuel A. Aguilar; Yuhan Kong; Shiqing Wei; Mingming Xu; Weimin Huang (Ocean Engineering, 2026)

Simultaneous leaching of Li, Rb, Cs from lepidolite via external electric field enhanced alkali leaching - Kun Xu; Mingming Yu; Heyue Niu; Yusufujiang Mubula; Zhehan Zhu; Di Han; Jingzhong Kuang; Lingguo Meng; Guichun He (Minerals Engineering, 2026)

Particle Type- and Morphology-Associated Neurotoxicity of Microplastics and Nanoplastics via Divergent PPARγ Modulation in Zebrafish - Chenchen Han; Lixia Peng; Xinlei Guo; Yaqi Yu; Mingming Niu; Willie J.G.M. Peijnenburg; Zhiqiang Li; Xilin She; Chuanhong Wu; Lianzhen Li (Journal of Hazardous Materials, 2026)

A combined lipidomics and flavoromics approach reveals that enzymatic interesterification improves the flavor stability of stored grass carp (Ctenopharyngodon idella) oil - Bin Peng; Linchuan Xu; Huijuan Zhou; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Food Research International, 2026)

Epigallocatechin Gallate (EGCG) Inhibits Singapore Grouper Iridovirus (SGIV) Infection by Interfering With Viral Life Cycle and Modulating Host Cell Cycle G2/M Checkpoint - Tianhong Zhao; Jinkun Xie; Chen‐Ao Li; Mingzhu Liu; Qing Yu; Lin Huang; Yanxia Gao; Mingming Zhao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a highly pathogenic virus that causes substantial economic losses in marine grouper aquaculture, and effective antiviral agents are currently lacking. In this study, the anti‐SGIV activity of epigallocatechin gallate (EGCG), a natural compound from green tea, was evaluated and its underlying mechanisms were investigated. Cytotoxicity assays showed that EGCG at concentrations up to 12.5 μg/mL was safe for grouper spleen (GS) cells. EGCG treatment reduced viral MCP and VP19 mRNA expression in a dose‐dependent manner, indicating its anti‐SGIV activity. Mechanistic studies revealed that EGCG directly impaired SGIV particle infectivity and interfered with viral adsorption, entry, and intracellular replication. Network pharmacology analysis identified overlapping genes between EGCG targets and SGIV‐induced differentially expressed genes, with enrichment pathways related to cell cycle regulation, particularly the G2/M checkpoint. Further studies showed that SGIV infection upregulated the G2/M checkpoint regulators WEE1 and CHEK2, and EGCG treatment reversed these dysregulations, suggesting that EGCG alleviates SGIV‐induced G2/M arrest. In vivo, EGCG treatment significantly reduced viral load in infected groupers and improved survival rate. Collectively, these findings demonstrate that EGCG exerts potent anti‐SGIV activity both in vitro and in vivo by directly targeting multiple steps of the viral life cycle and modulating host cell cycle G2/M checkpoint pathways, highlighting its potential as a natural therapeutic agent against SGIV infection.

Corrigendum to "Study on the detection method of Brucella differential type PCR" [Vet. Immunol. Immunopathol. 293 (2026) 111075] - Yajie Luo; Yun Qin; Hao Zhang; Yanmin Zhang; Jing Lu; Xiaofang Liu; Chunxia Liu; Luchao Zuo; Zhiyuan Lv; Hao Liu; Mingming Xie; Yu Yu; et al. (Veterinary Immunology and Immunopathology, 2026)

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Hybrid gels based on zein nanoparticles, pectin and hydroxypropyl guar gum co-stabilized MLCT-rich Pickering emulsion gels and beeswax oleogels for functional fat substitutes - Zhouliang Sun; Yufei Zhang; Yi Zhang; Huanyu Zheng; Chen Yu; Kai Shan; Yang Li; Mingming Zheng (Carbohydrate Polymers, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Widespread increase in root zone water use exacerbates water stress in cultivated regions - Shuping Du; Shanhu Jiang; Liliang Ren; Hao Cui; Yongwei Zhu; Miao He; Mingming Ren; Chong-Yu Xu (Agricultural and Forest Meteorology, 2026)

Synergistic Fe3+ coordination optimization and electron transfer: boosting photo-Fenton performance of carbon dots for advanced water treatment - Yuezi Huang; Shengyi Wang; Guanchen Wang; Honglin Hou; Wanneng Yu; Yuxiu Dong; Cheng Chen; Mingming Guo (Journal of Cleaner Production, 2026)

Enhanced selective removal of benzohydroxamic acid from flotation wastewater by ferrihydrite: Insights into performance and mechanism - Xiulin Wang; Jingzhong Kuang; Wenxin Hua; Lufeng Zeng; Mingming Yu; Lingguo Meng (Journal of Environmental Management, 2026)

Effect of PET-MPs exposure on the toxicology of PCOS: a multi-platform computational toxicology investigation - Hai Bai; Yuxiao Jiang; Bozhi Zhu; Jing Huang; Yu Zhang; Xunrui Liu; Liying Ge; Shanshan Zhang; Yue Shi; Mingming Wang (Molecular Diversity, 2026)

Elucidating the Effect of Perilla frutescens Extracts with Various Solvents Treatment on the Physicochemical Properties and Flavor Characteristics of Grass Carp Cubes During Cold Storage - Hao Wang; Chengwei Yu; Yanan Sun; Mengke Tian; Bizhen Zhong; Bin Peng; Mingming Hu; Jinlin Li; Zongcai Tu (Journal of Aquatic Food Product Technology, 2026)

Study on the detection method of Brucella differential type PCR - Yajie Luo; Yun Qin; Hao Zhang; Yanmin Zhang; Jing Lu; Xiaofang Liu; Chunxia Liu; Luchao Zuo; Zhiyuan Lv; Hao Liu; Mingming Xie; Yu Yu; et al. (Veterinary Immunology and Immunopathology, 2026)

A numerical simulation investigation into the hydrodynamic behavior of propellers considering the effects of longitudinal vibration of the shafting system - Yakun Lu; Changlin Meng; Donghua Wang; Zhixiang Li; Yibin Guo; Bin Chen; Mingming Wang; Jiapeng Yu; Hanzhang Xu; Wanyou Li (Ocean Engineering, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Pectin oligosaccharides stabilize sea cucumbers against heat-induced deterioration - Shangju Yang; Wenhui Hao; Jiaqi Yu; Mingming Wang; Ying Xu; Xun Sun (Food Hydrocolloids, 2026)

Chondrocyte-targeting hydrogel loaded with puerarin limits osteoarthritis development by maintaining mitochondrial function - Yunpeng Wan; Kai Shen; Jishi Jiang; Dan li; Mingming Ma; Chengmin Liang; Jie Cao; Bin Liu; Yu Ge; Lei Li; Yaguang Wang; Haiyang Yu (Chemical Engineering Journal, 2026)

Neural stem cell-derived exosomal PA2G4 induces ANXA2 degradation to promote mitophagy and alleviate neuronal oxidative stress in cerebral ischemia/reperfusion - Mingming Dai; Tingting Lu; Jinghao Li; Hang Yu (Apoptosis, 2026)

Much Larger Whole‐Profile Soil Organic Carbon Stocks on the Qinghai‐Tibet Plateau Than Previously Reported - Jiajun Mao; Shuai Zhang; Mingming Wang; Wu Yu; Feng Liu; Yuanhe Yang; Mishra Umakant; Zhou Shi; Zhongkui Luo (Global Change Biology, 2026)
The Qinghai‐Tibet Plateau (QTP), often referred as Earth's “Third Pole,” is warming nearly twice the global average, potentially amplifying carbon–climate feedbacks to a greater extent than in most other regions. However, substantial uncertainties remain regarding the magnitude, spatial distribution, and environmental controls of the region's soil organic carbon (SOC) stocks. Here we compiled a comprehensive dataset of 2442 soil profiles across the QTP and integrated it with high‐resolution (90 m) environmental covariates to generate spatially explicit, depth‐resolved SOC stock estimates using machine learning models. Independent validation using newly collected whole‐profile SOC measurements ( n = 53) demonstrated substantially improved predictive accuracy compared to existing global and regional mapping products (e.g., SoilGrids, HWSD, and WISE). Specifically, our estimates reached coefficients of determination ( R 2 ) of 0.63 and 0.49 for the 0–0.3 m topsoil and 0.3–1.0 m subsoil, respectively; while the existing mapping products only reached a R 2 of 0.01–0.35 in the topsoil and 0.01–0.15 in the subsoil. Across the QTP, our results estimated a total SOC stock of 62.0 (95% confidence interval: 54.9–69.1) Pg C within the top 2 m of soil, with more than 60% stored below 0.3 m depth. This value is much larger than most of the existing estimates in the same region. Alpine meadows ecosystems accounted for approximately 38% of the total SOC stock, primarily due to their extensive coverage, while swamp meadow ecosystems exhibited the highest SOC densities. Spatial uncertainty was highest in the sparsely sampled northwestern QTP. Contemporary climate and paleoclimate factors collectively contributed over 50% to the explained variance in SOC distribution across the soil profile, highlighting the dominant role of climatic factors on SOC spatial pattern. This spatially explicit, high‐resolution SOC mapping provides a baseline for constraining carbon–climate feedback assessments on the QTP and underscores the region's heightened vulnerability to ongoing climate warming.

Urban underground car parking: present past and future - Lingxiang Wei; Mingming Liu; Nikolai Bobylev; Junyuan Ji; Lei Yao; Tian Li; Lei Yu (Tunnelling and Underground Space Technology, 2026)

Selective separation mechanism of a metal inhibitor complex for scheelite and calcite: The structural stability of Fe3+-pyrogallol complex - Wenxin Hua; Jingzhong Kuang; Zheyu Huang; Lei Wang; Man Chen; Chenyang Zhang; Mingming Yu; Lingguo Meng (Minerals Engineering, 2026)

Numerical investigation on the influence of temperature on combustion and emission characteristics of NH3/H2/CH4 mixtures under gas turbine conditions - Yanfei Zhang; Qing Hao; Mingming Huang; Zhenxian Liu; Qin Li; Zewen Yu; Jianfang Du; Xiao Zhang; Zhuoming Xiong; Qingkui Zhang; Yumeng Cao; Haoxi Sha (Fuel, 2026)

Different polyphenols improve the gel properties by altering the crystal density of short- and long-chain acyl triacylglycerols oleogels - Fang Hu; Yingying Zhang; Jialing Long; Dayang Zhu; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Shiyi Li (Food Chemistry, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Bio-based vitrimer with superior rigidity-flexibility balance and high reprocessability fabricated via dynamic crosslinking and stepwise hot-pressing strategy - Mingming Yu; Rongbin Xiao; Xiaolei Wang; Haigang Xiao; Lin Fang; Wang Xie; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Simultaneous Quantification of Coenzyme Q10 and Vitamin E in Softgel Capsules Using Validated 1H NMR Spectroscopy - Yixuan Wang; Mingming Yu; Cong Wang (Journal of Ocean University of China, 2026)

Optimal Water Distribution Model for Channels With Complex Supply and Demand Relationships - Yu Fan; Zhanyi Gao; Haorui Chen; Mingming Yang; Weixian Zhang; Yifan Wang; Zhijun Jia (Irrigation and Drainage, 2026)
To address the complex many‐to‐many supply–demand relationship between channels and field plots in irrigation systems (where a single channel can irrigate multiple plots and a single plot can receive water from multiple channels), this study developed a novel optimized water distribution model for channel systems. The model innovatively incorporates channel water transmission time parameters to precisely control irrigation sequences and adopts a ‘rotation irrigation between groups—continuous irrigation within groups’ operational mode (based on an improved 0–1 model framework). Setting the optimization goal of synchronized water distribution completion among rotation groups enhances management efficiency. In the empirical study of the Bojili Irrigation District, the model optimized the lateral channel system by dividing it into two rotation groups, achieving the following: (i) The time difference in water distribution completion among channels within each group was significantly reduced (achieving synchronized completion); (ii) a substantial decrease in the flow adjustment frequency of branch channels. The results demonstrate that this model not only effectively resolves water distribution challenges in complex supply–demand networks but also provides scientifically sound and operational distribution schemes, offering decision‐making support for precision management in irrigation districts.

Response mechanisms of spatial ecological patterns in the Yellow River estuary to water-sediment regulation scheme - Shouwen Qiao; Yongqing Yu; Linfeng Wang; Mingming Zhu; Xiang Zheng; Xiuxia Wang; Guangxin Cui; Fan Li; Yanyan Yang (Regional Studies in Marine Science, 2026)

Recovery of rare earths from rare earth molten salt electrolytic slag using atmospheric pressure alkaline leaching enhanced by ultrasonic - Yusufujiang Mubula; Mingming Yu; Huashan Yan; Heyue Niu; Kun Xu; Zhehan Zhu; Jingzhong Kuang; Guangjun Mei (Minerals Engineering, 2026)

Oxygen–deficient Fe2O3 bearing pyridine n moieties for spatially decoupled selective H2S oxidation into sulfur at intermediate temperatures - Mingming Guo; Ruiyi Wang; Jia-nan Gu; Yu Feng; Furong Guo; Guangming Zhan; Lijun Wang; Kan Li; Hao Li; Jinping Jia; Tonghua Sun (Journal of Hazardous Materials, 2026)

Effects of ultrasound on zein-procyanidin composite nanoparticles: Interaction force, structure, emulsifying properties and interfacial behaviors - Junxia Wang; Qiufang Liang; Mingming Zhong; Yufan Sun; Yuxuan Liu; Yongjun Zhao; Kai Yu; Arif Rashid; Abdul Qayum; Xiaofeng Ren (Food Chemistry, 2026)

Light-driven oxygen supersaturation controls microbial resilience in microalgal-bacterial granular sludge systems: Novel intermittent regulation strategy for carbon–neutral wastewater treatment - Liaofan Tang; Yufen Xue; Ning Shi; Mingming Gao; Fangying Yu; Wenxin Wang; Yuqing Zhang; Shuguang Wang; Xinhua Wang (Bioresource Technology, 2026)

Characteristics and Antibacterial Activity of Staphylococcus aureus Phage-Derived Endolysin LysP4 - Mingming Gao; Xinting Yu; Cuiping Yang; Zhiqiang Mi; Changqing Bai; Chuanbin Liu; Huiying Liu (Probiotics and Antimicrobial Proteins, 2026)

A systematic review of metro and low-carbon city: Bibliometric analysis, metro decarbonization and research prospects - Lingxiang Wei; Mingming Liu; Junyuan Ji; Dongjun Guo; Jun Huang; Hao Zuo; Tian Li; Lei Yu (Urban Climate, 2025)

Alkyl-modified polyacrylic acid hydrogel tablets for Targeted retention and reduced droplets drift of glyphosate isopropylamine salt - Yingxi Zhang; Hanghang Zhang; Chong Cao; Pengyue Zhao; Mingming Yin; Manli Yu; Qiliang Huang; Lidong Cao (Journal of Cleaner Production, 2025)

Spatio-temporal heterogeneity of quality attributes and flavors in grass carp (Ctenopharyngodon idella) cubes during deep frying: Key metabolic evidence - Hao Wang; Ning Cui; Bin Peng; Chengwei Yu; Bizhen Zhong; Mingming Hu; Jinlin Li; Zongcai Tu (Food Chemistry, 2025)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Efficient cross-seasonal utilization of solar energy driven by sodium acetate supercooled phase change materials - Mingming Pan; Lingling Wang; Debing Wang; Jiarui Du; Huaqing Xie; Wei Yu; Jingsan Xu (Chemical Engineering Journal, 2025)

Generation of reactive nitrogen species for ultrasound-catalyzed tumor treatment through cascade reaction by self-supplied H2O2 nano-reactor - Hao Wu; Zhiping Zhang; Zhao Wang; Lei Yu; Quanxiang Han; Yurong Guo; Mingming Gao; Yingying Jing; Liwei Chen; Xing Gao; Yen Leng Pak; Jibin Song (Chemical Engineering Journal, 2025)

Recent progress in the microbial production of Xylanase - Shoufeng Wang; Mingming Zhao; Yu Zheng; Hualan Zhou; Wenjie Cong; Jianguo Zhang (World Journal of Microbiology and Biotechnology, 2025)

Impacts of the water-sediment regulation scheme on nutrient inputs in the Yellow River estuary and assessment of marine purification capacity - Shouwen Qiao; Yongqing Yu; Linfeng Wang; Mingming Zhu; Yanyan Yang (Marine Environmental Research, 2025)

Effect of the downward bevel angle on the particle radial migration behaviour and secondary flow in spiral separators - Meng Lingguo; Gao Shuling; Liu Tianlin; Kuang Jingzhong; Yu Mingming (Minerals Engineering, 2025)

Enhancement of sulforaphene stability via hydroxypropyl methylcellulose-based solid dispersions: exploiting hydrophobic cavities and hydrogen bonding-mediated water sequestration - Purui Yu; Mintong Tian; Zhe Shang; Meng Zhou; Zehua Li; Mingming Li; Huan Gao; Qipeng Yuan (Carbohydrate Polymers, 2025)

Study on degradation pathway of macromolecules and mechanistic insights of hydrochar formation during hydrothermal treatment: From model compounds to food waste - Mingming Yang; Xueli Chen; Yifei Wang; Lu Ding; Guangsuo Yu; Fuchen Wang (Biomass and Bioenergy, 2025)

Establishing a chromium/periodate advanced oxidation process for trace organic contaminants removal: The positive effect of Cr(III) complexation - Jing Wang; Xinhua Wang; Shuqi Li; Yu Liu; Shu-Guang Wang; Mingming Gao (Journal of Hazardous Materials, 2025)

Effects of acidity & electron donor composite factors metabolism in SRBs flora — Electron donor is the main controlling factor - Shuaixian Mao; Yunfeng Zhao; Wenqing Liu; Minghan Zhang; Ruimin Li; Qiyu Guo; Zhiyong Zeng; Haiyan Wang; Peimeng Su; Mingming Zhang; Caihong Yu (Journal of Environmental Chemical Engineering, 2025)

Porous MXene/transition metal dichalcogenide heterostructure anodes with accelerated charge transfer kinetics for high-energy and long-life sodium-ion hybrid capacitors - Mingming Gao; Jundong Shao; Ying Huang; Xinyi Duan; Sheng Yang; Faxing Wang; Feng Yu; Zaichun Liu; Yao Gao; Panpan Zhang; Yuping Wu; Xing Lu (Chemical Engineering Journal, 2025)

Wet-chemical-assisted 3D printing of functionalized comb structures for efficient and scalable fog harvesting - Jiang Shang; Yuanyuan Hou; Shen Yu; Yongling Wu; Mingming Liu (Chemical Engineering Journal, 2025)

Application, mechanism and future prospect of electric field in fish processing and preservation: A review - Bin Peng; Huimin Ma; Linchuan Xu; Hanhao Zhou; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Trends in Food Science & Technology, 2025)

Functional oleogels constructed by short- and long-chain acyl triacylglycerols: Characterization and in vitro simulated digestion - Fang Hu; Liwen Zhang; Yan Zhu; Suyuan Zhao; Wei Xu; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Shiyi Li (Food Chemistry, 2025)

Selecting a representative tea for risk assessment of pesticide residue in tea:Afidopyropen as a case - Mingming Guo; Zhaoqun Li; Yujie Qin; Kexin Qian; Chi Su; Jiawei Yu; Hezhi Sun; Xinzhong Zhang; Xinru Wang; Mei Yang; Fengjian Luo; Zongmao Chen; et al. (Food Chemistry, 2025)

Gas Hydrate Exploration Using Deep-Towed Controlled-Source Electromagnetics in the Shenhu Area, South China Sea - Jianping Li; Zhongliang Wu; Xi Chen; Jian’en Jing; Ping Yu; Xianhu Luo; Mingming Wen; Pibo Su; Kai Chen; Meng Wang; Yan Gao; Yao Zhang (Journal of Marine Science and Engineering, 2025)
This study presents the first application of a deep-towed transmitter–receiver marine controlled-source electromagnetic (TTR-MCSEM) system for gas hydrate exploration in the Shenhu area of the South China Sea. High-resolution electromagnetic data were acquired along a 13 km transect using dynamic source–receiver offsets and a 500 A transmitter. The results reveal the following: (1) unprecedented near-seafloor resolution (20~100 m) for the precise delineation of hydrate-bearing caprock, surpassing conventional ocean-bottom electromagnetic systems; (2) laterally continuous high-resistivity anomalies (~10 Ω·m) extending from the base of the gas hydrate stability zone to the seafloor, which correlate with seismic bottom-simulating reflector (BSR) distributions and suggest heterogeneous hydrate saturation; and (3) fault-controlled fluid migration pathways that supply hydrate reservoirs and lead to seabed methane seepage at structural highs. Through 2D inversion, we show that the inverted resistivity values (~10 Ω·m) are slightly higher than those obtained from resistivity logs (~5 Ω·m). Saturation values derived from inverted resistivity exhibit remarkable consistency with well-log-based measurements. The high efficiency of the system confirms its potential for the transformative quantitative assessment of hydrate systems, seafloor massive sulfides, and marine geohazards.

A Self-Adapting Polygenic Risk Score Model Improves Risk Prediction of Venous Thromboembolism in Han Chinese Cohorts - Zhaoman Wan; Zhu Zhang; Mingming Su; Haobo Li; Yu Zhang; Xinlei Zhang; Aiping Wu; Taijiao Jiang; Peng Zhang; Zhenguo Zhai (Phenomics, 2025)

Critical roles of rare species in the anaerobic ammonium oxidizing bacterial community in coastal sediments - Yu Zhang; Mingming Chen; Rui Du; Ehui Tan; Shuh-Ji Kao; Yao Zhang (Marine Life Science & Technology, 2025)
Anaerobic ammonium oxidation (anammox) plays a critical role in nitrogen loss in estuarine and marine environments. However, the mechanisms underlying the formation and maintenance of the anammox bacterial community remain unclear. This study analyzed the anammox bacterial diversity, community structure, and interspecific relationships in three estuaries along the Chinese coastline —the Changjiang Estuary (CJE), the Oujiang Estuary (OJE), and the Jiulong River Estuary (JLE) — as well as the South China Sea (SCS) to elucidate their community assembly mechanisms. The results indicated that the anammox bacterial community exhibited the highest ammonium concentration as well as the Shannon’s diversity index reflecting both species richness and evenness in the JLE. The lowest Shannon index was observed in the SCS. However, the anammox bacterial species richness was greatest in the CJE. Candidatus Scalindua was the predominant anammox bacteria identified in the coastal sediments, especially in the SCS sediments. Candidatus Brocadia and Candidatus Kuenenia were more abundant in the estuarine sediments, particularly in JLE, than in the SCS. Phylogenetic analysis revealed distinct differentiation among Candidatus Scalindua, Candidatus Brocadia, and Candidatus Kuenenia, with the former exhibiting a greater level of diversity. There was significant spatial heterogeneity in the anammox bacteria across the four regions, characterized by distinct distribution patterns for rare species. Low-abundance (rare) bacteria thrived in their native habitats, whereas abundant taxa displayed greater dispersal capabilities. An analysis of the community assembly mechanism suggested that ecological drift predominantly shaped the overall anammox bacterial community in the coastal sediments. Rare species were more susceptible to dispersal limitations and environmental selection. Co-occurrence network analysis identified Candidatus Scalindua as a keystone genus and highlighted that rare species may play a crucial role in maintaining the ecological stability of the anammox bacterial community in coastal sediments.

Performance and mechanism analysis of a novel conjunctival composite dust suppressant for metal mines - Zhian Huang; Keying Meng; Jiaze Ren; Rongxia Yu; Mingming Fu; Gaowen Wang; Yinghua Zhang; Hongsheng Wang; Jinyang Li; Ye Xu; Md Yasin; Asim Farooq (Process Safety and Environmental Protection, 2025)

Phylogenetic relationship, genomic heterogeneity, and population structure of Yersinia enterocolitica biotype 1A isolated from pork and poultry meat - Mingming Yu; Yimeng Wang; Xiaoyan Hao; Lidan Jiang; Dehui Liu; Yongbo Sun; Jin Xu; Zixin Peng (Food Research International, 2025)

Identification, characterization, and molecular docking of immunomodulatory peptides in Astragalus (Astragalus membranaceus (Fisch.)Bge) seed protein hydrolysates - Yu Zhao; He Teng; Zhongxian Yu; Shuai Shao; Guangzhe Li; Mingming Yan (Food Chemistry, 2025)

Synergistic estimation of mangrove canopy height across coastal China: Integrating SDGSAT-1 multispectral data with Sentinel-1/2 time-series imagery - Mingming Jia; Rong Zhang; Chuanpeng Zhao; Yaming Zhou; Chunying Ren; Dehua Mao; Huiying Li; Genyun Sun; Hongsheng Zhang; Wensen Yu; Zongming Wang; Yeqiao Wang (Remote Sensing of Environment, 2025)

Comprehensive lipidomics and flavoromics reveals the accelerated oxidation mechanism of fish oil from silver carp (Hypophthalmichthys molitrix) viscera during heating - Jinlin Li; Junru Bai; Liping Yuan; Huijuan Zhou; Linchuan Xu; Chengwei Yu; Mingming Hu; Zongcai Tu; Bin Peng (Food Chemistry, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

Insights on enhancing the application of glucoraphenin in radish based on the decomposition mechanism - Mintong Tian; Zehua Li; Purui Yu; Meng Zhou; Mingming Li; Guanghao Li; Qipeng Yuan (Food Bioscience, 2025)

Vanadium nitride quantum dots-based nanozyme in synergy with immune checkpoint blockade for enhanced cancer immunotherapy through vanadate and nitric oxide - Haoqi Pan; Xiaoning Yu; Qing He; Lixia Yi; Mingming Xiao; He Xu; Qingcai Meng; Jie Hua; Dong Cen; Si Shi; Xianjun Yu (Chemical Engineering Journal, 2025)

The Innovation Paradox in Emerging Pharmaceutical Markets: Barriers and Opportunities for Sustainable Development - Frederico Severino Martins; Sivacharan Kollipara; Praveen Sivadasu; Mingming Yu; Patricia Severino; Eliana Souto (Pharmaceutical Research, 2025)

Regulation of innate lymphoid cell by microbial metabolites - Hongji Tao; Jingjing Geng; Long Bai; Dan Su; Yu Zhao; Guifang Xu; Mingming Zhang (Journal of Molecular Medicine, 2025)

Highly efficient enzymatic enrichment of n-3 polyunsaturated fatty acid glycerides via interfacial biocatalysis in Pickering emulsions - Liumei Wu; Dongming Li; Fuyang Bi; Chao Yu; Yufei Zhang; Mingming Zheng (Food Chemistry, 2025)

Global Avian Frugivore‐Fruit Trait Matching Decreases Toward the Tropics - Mingming Zhang; Yang Wang; Xifu Yang; Yueqin Yang; Fei Yu; Xianfeng Yi (Global Change Biology, 2025)
Trait matching, the phenomenon where ecological interactions are mediated by compatibility, constitutes a cornerstone of frugivore–fruit interaction network dynamics. Given that biotic interactions have long been hypothesized to be more intense or specialized in the tropics, the intensity of trait matching patterns might likewise exhibit a latitudinal gradient in frugivory networks, yet this remains unverified. Here, we established a dataset encompassing 200 avian frugivorous networks to explore the relationships between the body mass and gape size of frugivore birds and fruit traits (size and color) on a global scale. Our results indicated that frugivore traits were closely associated with fruit traits regardless of the climate, demonstrating a biotic match between the two counterparts. We detected a significant decrease in frugivore–fruit trait matching toward the tropics, which challenges prevailing concepts considering the high biodiversity therein. Our structural equation modeling clarified that latitude and temperature exert an indirect influence on trait matching by affecting gape size and fruit traits. These discoveries emphasize the impact of the latitudinal gradient of temperature in driving the observed patterns of trait matching. The weaker trait matching in tropical regions may suggest more complex interactions therein and also highlights the potential for altered network structures amid global climate change.

Sus scrofa RNase L inhibits PRRSV replication by activation of type I IFN signaling pathway and apoptosis - Xiangju Wu; Xiaoyan Cong; Ping Jiang; Mingming Zhou; Ying Yu; Dandan Jiang; Yue Hu; Juntong Li; Jinxia Zhang; Ying Cao; Haowen Zhang; Yijun Du; et al. (Veterinary Microbiology, 2025)

Study on the nutritional relationships in mycelia and fruiting bodies of Hypsizygus marmoreus under defined nutrient conditions - Jianqiu Chen; Mingming Yu; Chun Yang; Zenan Huang; Lizhang He; Jiaojiao Bian; Shujing Sun; Jiahuan Li (Food Chemistry, 2025)

Multifunctional waterborne polyurethane-cellulose nanofiber composite: Realizing ultrarobust, photoluminescence and swift self-healing via multi-dynamic bonding - Xia Zhang; Fuhao Dong; Mingming Yu; Xu Xu; He Liu; Haiqin Lu (Chemical Engineering Journal, 2025)

Mechanism and biodegradability of melanoidins formed in hydrothermal process: From model compounds to food waste - Mingming Yang; Xueli Chen; Lu Ding; Fuchen Wang; Guangsuo Yu (Bioresource Technology, 2025)

The growth and nutrient removal properties of heterotrophic microalgae using volatile fatty acids under different nitrogen forms and its application in actual acid-producing wastewater - Cong Jia; Na Liu; Lei Chen; Wenbao Yan; Qi Zhao; Jie Li; Ze Yu; Mingming Song; Chongqing Xu; Xiaozhe Song (Journal of Environmental Chemical Engineering, 2025)

Highly efficient photocatalytic Microcystin-LR elimination using magnetic recyclable nanocomposite ZnO/Fe3O4/Bi2WO6/RGO and its toxicity assessment - Mingming Zhan; Ganlin Hu; Yu Hong; Zhi Fang; Daping Qiu (Journal of Environmental Chemical Engineering, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Fate of polycyclic aromatic hydrocarbon (PAHs) in urban lakes under hydrological connectivity: A multi-media mass balance approach - Shizhao Zhang; Xinli Xing; Haikuo Yu; Minkai Du; Yuan Zhang; Peng Li; Xin Li; Yanmin Zou; Mingming Shi; Weijie Liu; Shihua Qi (Environmental Pollution, 2025)

Improving efficiency and stability of wide-bandgap perovskite solar cells and four-terminal tandems with iso-propylammonium 2D passivator - Mingming Hu; Shengjie Du; Zhiqiu Yu; Guoyi Chen; Jiwei Liang; Qingbin Cai; Guojia Fang (Chemical Engineering Journal, 2025)

Simultaneous Quantification of Total Antibody and Conjugated Payload for DS001 in Rat Serum Using a Hybrid Immuno-Capture LC–MS/MS - Xiong Yu; Weiqiang Li; Wensi Huang; Bo Xiao; Jing Long; Qi Wang; Guifeng Wang; Chunhe Wang; Mingming Yu; Jinghua Yu; Xingxing Diao (The AAPS Journal, 2025)

The possible inhibition mechanism of low salt dry-curing on volatile flavor deterioration in refrigerated grass carp (Ctenopharyngodon idella) blocks: Metabolomics and microorganisms - Bin Peng; Linju Xu; Chengwei Yu; Mingming Hu; Bizhen Zhong; Zongcai Tu; Jinlin Li (Food Chemistry, 2025)

Corrigendum to “Impact of several sludge dewatering conditioners on municipal sludge pyrolysis properties, kinetics, by-products, and environmental risk assessment” [Sci. Total Environ. 951 (2024)1-18 / 175653] - Guiying Xu; Xiaoxuan Yang; Feihong Yu; Jiangnan Mei; Mingming Liu; Mingsong Li; Teng Zhu; Baizeng Fang (Science of The Total Environment, 2024)

Determination of the 15 compounds include both pesticides and plant growth regulators (PGRs) in cherry by liquid chromatography triple quadrupole mass spectrometry (LC-MS-MS) - Mingming Su; Yang Lu; Yu Yang; Yao Sun; Zhenlin Dong; Weijian Shen; Lingling Jiang; Yuyang Zhang (Food and Humanity, 2024)

Quantifying physiological health efficiency and benefit threshold of greenspace exposure in typical urban landscapes - Yuenan Jin; Zhaowu Yu; Gaoyuan Yang; Xihan Yao; Mingming Hu; R.P. Remme; P.M. van Bodegom; Joeri Morpurgo; Yunfeng Huang; Jingyi Wang; Shenghui Cui (Environmental Pollution, 2024)

A rare KMT2A::CBL transcript in an acute monoblastic leukemia patient with an unfavorable outcome - Jinglei Yu; Fengmei Song; Mingming Zhang; Pingnan Xiao; Jingjing Feng; Ruimin Hong; Yongxian Hu; He Huang; Guoqing Wei (Molecular Biology Reports, 2024)
Background Lysine [K] methyltransferase 2A ( KMT2A , previously known as MLL ) gene rearrangements are common in acute leukemias of various lineages and are associated with features such as chemotherapy resistance and rapid relapse. KMT2A::CBL is a rare fusion of unknown pathogenesis generated by a unique interstitial deletion of chromosome 11 that has been reported across a wide age range in both acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) patients. The leukemogenic effect of the KMT2A::CBL rearrangement and its association with clinical prognosis have not been well clarified. Methods and results We report the case of a 64-year-old female who was diagnosed with acute monoblastic leukemia (M5a) and who acquired the rare KMT2A::CBL fusion. The patient received multiple cycles of therapy but did not achieve remission and eventually succumbed to severe infection and disease progression. Additionally, we characterized the predicted KMT2A-CBL protein structure in this case to reveal the underlying leukemogenic mechanisms and summarized reported cases of hematological malignancies with KMT2A::CBL fusion to investigate the correlation of gene rearrangements with clinical outcomes. Conclusions This report provides novel insights into the leukemogenic potential of the KMT2A::CBL rearrangement and the correlation between gene rearrangements and clinical outcomes.

Impact of several sludge dewatering conditioners on municipal sludge pyrolysis properties, kinetics, by-products, and environmental risk assessment - Guiying Xu; Xiaoxuan Yang; Feihong Yu; Jiangnan Mei; Mingming Liu; Mingsong Li; Teng Zhu; Baizeng Fang (Science of The Total Environment, 2024)

Characterization and functions of Myeloblastosis (MYB) transcription factors in cucurbit crops - Mingming Sun; Xuemei Xiao; Khuram Shehzad Khan; Jian Lyu; Jihua Yu (Plant Science, 2024)

Cytology, metabolomics, and proteomics reveal the grain filling process and quality difference of wheat - Fang Li; Chao Cui; Chenyang Li; Yan Yu; Quan Zeng; Xiaoyan Li; Wanchun Zhao; Jian Dong; Xiang Gao; Jishan Xiang; Dingguo Zhang; Shanshan Wen; et al. (Food Chemistry, 2024)

MXene-based dual-gated multifunctional nanodrug induced ferroptosis and modulated tumor microenvironment to treat pancreatic cancer - Xiaoning Yu; Haoqi Pan; Qing He; Jing Yang; Mingming Xiao; Jin Xu; Wei Wang; Xianjun Yu; Si Shi (Chemical Engineering Journal, 2024)

Controllable heat release of supercooled Erythritol-based phase change materials for long-term thermal energy storage - Mingming Pan; Debing Wang; Lingling Wang; Nannan Dong; Huaqing Xie; Wei Yu (Chemical Engineering Journal, 2024)

Unraveling programmable motion of MXene/polyurethane motor driven by the near-infrared light - Yu Xu; Haoyu Qi; Mingming Sun; Zongxu Liu; Qing Liu; Kang Li; Wei Guo (Chemical Engineering Journal, 2024)

Multi-omics reveals the particle size effect of nanoplastics on the hepatopancreas and intestinal toxicity of crustacean model Neospoda palmata - Mingming Han; Tian Zhu; Zihan Zhou; Yiming Li; Cigang Yu; Ji Liang; Hong Wang; Qin Si; Qichen Jiang (Science of The Total Environment, 2024)

Geochemical and detrital zircon U Pb geochronology of the qigequan formation in the yuejin 2 area: Implications for tectonics and uranium sources - Chao Zhang; Shanbo Wang; Reng'’an Yu; Deqing Ma; Mingming Wang; Zhifeng Zuo; Jiarun Tu (Lithos, 2024)

Development of dual-channel starch-based film incorporated with betanin@β-cyclodextrin inclusion complex and berberine for indicating shrimp freshness - Zan Yang; Zheng Wang; Pan Liu; Wenya Liu; Yingran Xu; Yibin Zhou; Zhenyu Yu; Mingming Zheng; Yaqing Xiao; Yingnan Liu (Food Chemistry, 2024)

Transcription Factor TFAP2B Exerts Neuroprotective Effects Targeting BNIP3-Mediated Mitophagy in Ischemia/Reperfusion Injury - Yong Peng; Jiaoying Jia; Mingming Zhang; Wenjia Ma; Yan Cui; Mengqiang Yu (Molecular Neurobiology, 2024)

Nitenpyram in tea: Eco-friendly detection methodology and residue behavior - Huan Yu; Mingming Guo; Xinru Wang; Jiazhen Zhang; Hezhi Sun; Xinzhong Zhang; Mei Yang; Fengjian Luo; Luchao Wu; Li Zhou (Food Research International, 2024)

DEM investigation on the shear mechanical behavior of rock fractures with the same roughness level - Jiuyang Huan; Mingming He; Meishu Li; Zhiwen Wan; Weijia Yu; Weitao Huan; Mengdie Hu (Bulletin of Engineering Geology and the Environment, 2024)

Life cycle water and energy consumption and efficiency analysis of major crops in China - Mingming Yang; Yongnan Zhu; Yong Zhao; Cuimei Li; Yuliang Zhang; Yu Fan; Wenjing Yang; Miaoye Kang (Journal of Cleaner Production, 2024)

Lipidomics profile and volatile compounds of squids (Illex argentinus, Ommastrephes Bartram and Dosidicus gigas) in the Argentine, North Pacific Ocean, Equator and Peru by UPLC-triple TOF-MS and HS-SPME-GC-O-MS - Bin Peng; Jinlin Li; Chengwei Yu; Mingming Hu; Bizhen Zhong; Shengqi Shi; Zongcai Tu (Food Research International, 2024)

Gain-of-function variants in GSDME cause pyroptosis and apoptosis associated with post-lingual hearing loss - Yun Xiao; Lei Chen; Kaifan Xu; Meijuan Zhou; Yuechen Han; Jianfen Luo; Yu Ai; Mingming Wang; Yu Jin; Ruifeng Qiao; Shuhui Kong; Zhaomin Fan; et al. (Human Genetics, 2024)
Gasdermin E (GSDME), a member of the gasdermin protein family, is associated with post-lingual hearing loss. All GSDME pathogenic mutations lead to skipping exon 8; however, the molecular mechanisms underlying hearing loss caused by GSDME mutants remain unclear. GSDME was recently identified as one of the mediators of programmed cell death, including apoptosis and pyroptosis. Therefore, in this study, we injected mice with GSDME mutant (MT) and examined the expression levels to assess its effect on hearing impairment. We observed loss of hair cells in the organ of Corti and spiral ganglion neurons. Further, the N-terminal release from the GSDME mutant in HEI-OC1 cells caused pyroptosis, characterized by cell swelling and rupture of the plasma membrane, releasing lactate dehydrogenase and cytokines such as interleukin-1β. We also observed that the N-terminal release from GSDME mutants could permeabilize the mitochondrial membrane, releasing cytochromes and activating the mitochondrial apoptotic pathway, thereby generating possible positive feedback on the cleavage of GSDME. Furthermore, we found that treatment with disulfiram or dimethyl fumarate might inhibit pyroptosis and apoptosis by inhibiting the release of GSDME-N from GSDME mutants. In conclusion, this study elucidated the molecular mechanism associated with hearing loss caused by GSDME gene mutations, offering novel insights for potential treatment strategies.

Magnetic recyclable visible light-driven Bi2WO6/Fe3O4/RGO for photocatalytic degradation of Microcystin-LR: Mechanism, pathway, and influencing factors - Mingming Zhan; Yu Hong; Zhi Fang; Daping Qiu (Environmental Research, 2024)

Metabolomics unveil key pathways underlying the synergistic activities of aztreonam and avibactam against multidrug-resistant Escherichia coli - Xuefeng Zhou; Jiayuan Zhang; Jianqi Chen; Li Wang; Mingming Yu; Sherwin K. B. Sy; Hai Yang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

How the Water-Sediment Regulation Scheme in the Yellow River affected the estuary ecosystem in the last 10 years? - Shouwen Qiao; Yanyan Yang; Bochao Xu; Yang Yang; Mingming Zhu; Fan Li; Huaming Yu (Science of The Total Environment, 2024)

Complex Topology of Ubiquitin Chains Mediates Lysosomal Degradation of MrgC Proteins - Jiacheng Yu; Dan Li; Mingming Xie; Jun Xie; Zhen Wang; Xiaoping Gu; Zhengliang Ma; Yu’e Sun (Cell Biochemistry and Biophysics, 2024)

Hierarchical molecular sieve-based Ce-Ru oxide for enhanced catalytic oxidation of chlorobenzene: Insight into the synergistic effect of Ce and Ru, the role of molecular sieve - Chengwei Yu; Jia-nan Gu; Yixin Xue; Mingming Guo; Kan Li; Jinping Jia; Tonghua Sun (Process Safety and Environmental Protection, 2024)

Thymoquinone regulates microglial M1/M2 polarization after cerebral ischemia-reperfusion injury via the TLR4 signaling pathway - Bingxin Zhao; Sheng Zhang; Nashwa Amin; Jie Pan; Fei Wu; Guanghong Shen; Mingming Tan; Zongjie Shi; Yu Geng (NeuroToxicology, 2024)

Aquatic plants dominate the sources of long-chain n-alkanes in floodplain lakes in the middle and lower reaches of the Yangtze River - Xiaofang Yu; Mingming Zhang; Guang Yang; Linghan Zeng; Xu Chen; Xiaoxia Lü; Xianyu Huang (Chemical Geology, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Biomedical analysis of four fixation systems in treatment of type II traumatic spondylolisthesis of the axis: a finite element analysis - Zuoyao Long; Hailong Yu; Huifeng Yang; Mingming Guo; Lingzhi Meng; Hong Yuan; Liangbi Xiang; Qi Wang (Medical & Biological Engineering & Computing, 2024)

Mechanism of inactivation of Aspergillus flavus spores by dielectric barrier discharge plasma - Yaxin Wang; Mingming Yu; Yanli Xie; Weibin Ma; Shumin Sun; Qian Li; Yuhui Yang; Xiao Li; Hang Jia; Renyong Zhao (Toxicon, 2024)

Green catalysis for the production of n-butyl acetate over phosphotungstic acid-encapsulated metal-organic framework UiO-67 catalyst: Catalyst preparation, characterization and reaction kinetics - Tianlin Ma; Chengcheng Song; Hongliang Chen; Manyun Yin; Chunyang Su; Ningfei Guo; Yang Yao; Mingming Yu; Yujie Wang; Gangling Chen; Zhi Yun (Sustainable Chemistry and Pharmacy, 2024)

Soil microbial communities' contributions to soil ecosystem multifunctionality in the natural restoration of abandoned metal mines - Ting Li; Sichen Wang; Chang'e Liu; Yadong Yu; Mingming Zong; Changqun Duan (Journal of Environmental Management, 2024)

Contrasting effects of frugivore assemblages and phylogeny on global variation in fruit length and width - Fei Yu; Mingming Zhang; Yang Wang; Jalene M. LaMontagne; Xianfeng Yi (Global Ecology and Biogeography, 2024)
Aim The evolution of fruit size is poorly understood, though long‐standing hypotheses, the dispersal syndrome hypothesis and correlated evolution hypothesis, have highlighted the influence of frugivores and phylogeny on fruit size variation. Location Interaction networks were extracted from studies carried out in Asia, Europe, Africa, Hawaii, Australia, New Zealand and the Neotropics. Time Period Up to 50 years between 1970 and 2022. Major Taxa Studied Frugivores (birds and mammals) and fleshy‐fruited plants. Methods We compiled a global data set on fruit size (i.e. width and length) and plant traits (i.e. leaf area and plant height) for 349 fleshy‐fruited plants, and the body mass of frugivores from 326 interaction networks. We constructed a plant phylogeny from a mega‐tree containing 74,533 vascular plant species and we calculated Pagel's λ to assess the phylogenetic signal in plant traits and fruit size. Phylogenetic generalized linear mixed model (PGLMM) was used to reveal relationships between fruit size and plant traits as well as the body mass of interacting frugivores. We used phylogenetic partial R 2 s regression model to tease apart the effects of body mass of frugivores, leaf area, plant height and plant phylogeny on the evolution of fruit size. Results We show that the global variation in fruit width is better explained by frugivorous assemblages than by phylogeny and plant functional traits (leaf area and plant height). Despite the significant evolutionary correlation between fruit length and width, fruit length appears to be more phylogenetically constrained and less sensitive to frugivore‐driven selection than fruit width. Main Conclusion In light of the two original hypotheses, our study demonstrates a global phylogenetic constraint on fruit length and frugivore‐driven selection on fruit width, provides a novel mechanistic explanation for the evolution of fruit size across fleshy‐fruited plant species. Our findings contribute to a deeper understanding of the complex interplay between frugivory, phylogeny and plant traits in the evolution of fruit size, offering valuable insights into the broader context of published findings and hypotheses in this field.

Fluctuations of aquatic macrophytes in a shallow lake in eastern China over the last 1800 years: Evidence from n-alkanes - Mingming Zhang; Xiaofang Yu; Shiwei Jiang; Xin Zhou; Xianyu Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Understanding the degradation mechanisms of cyanide and starch in cassava flour during extrusion processing - Mingming Qi; Jialin Song; Lijun Jiang; Luxia Li; Mei Xu; Yueming Li; Shifeng Yu; Hongjun Li (Innovative Food Science & Emerging Technologies, 2024)

Insights into ball milling treatment promotes the formation of starch-lipid complexes and the relation between multi-scale structure and in vitro digestibility based on intermolecular interactions - Zongwei Hao; Huajian Xu; Yiyang Yu; Zongyan Gu; Yu Wang; Chao Li; Yaqing Xiao; Yingnan Liu; Kang Liu; Mingming Zheng; Yiqun Du; Yibin Zhou; et al. (Food Hydrocolloids, 2024)

Phosphorus-containing reactive compounds to prepare fire-resistant vinyl resin for composites: Effects of flame retardant structures on properties and mechanisms - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2024)

Recovery of valuable elements from solid waste with the aid of external electric field: A review - Yusufujiang Mubula; Mingming Yu; Delong Yang; Bo Lin; Yuting Guo; Tingsheng Qiu (Journal of Environmental Chemical Engineering, 2023)

Development and Validation of UHPLC-MS/MS Method for Quantifying of Agarotriose: An Application for Pharmacokinetic, Tissue Distribution, and Excretion Studies in Rats - Jiali Yue; Wei Cheng; Shutong Wei; Guilin Liu; Meichen Zhou; Zhihua Lv; Mingming Yu (Journal of Ocean University of China, 2023)

China's wetland soil organic carbon pool: New estimation on pool size, change, and trajectory - Yongxing Ren; Dehua Mao; Zongming Wang; Zicheng Yu; Xiaofeng Xu; Yanan Huang; Yanbiao Xi; Ling Luo; Mingming Jia; Kaishan Song; Xiaoyan Li (Global Change Biology, 2023)
Robust estimates of wetland soil organic carbon (SOC) pools are critical to understanding wetland carbon dynamics in the global carbon cycle. However, previous estimates were highly variable and uncertain, due likely to the data sources and method used. Here we used machine learning method to estimate SOC storage and their changes over time in China's wetlands based on wetland SOC density database, associated geospatial environmental data, and recently published wetland maps. We built a database of wetland SOC density in China that contains 809 samples from 181 published studies collected over the last 20 years as presented in the published literature. All samples were extended and standardized to a 1‐m depth, on the basis of the relationship between SOC density data from soil profiles of different depths. We used three different machine learning methods to evaluate their robustness in estimating wetland SOC storage and changes in China. The results indicated that random forest model achieved accurate wetland SOC estimation with R 2 being .65. The results showed that average SOC density of top 1 m in China's wetlands was 25.03 ± 3.11 kg C m −2 in 2000 and 26.57 ± 3.73 kg C m −2 in 2020, an increase of 6.15%. SOC storage change from 4.73 ± 0.58 Pg in 2000 to 4.35 ± 0.61 Pg in 2020, a decrease of 8.03%, due to 13.6% decreased in wetland area from 189.12 × 10 3 to 162.8 × 10 3 km 2 in 2020, despite the increase in SOC density during the same time period. The carbon accumulation rate was 107.5 ± 12.4 g C m −2 year −1 since 2000 in wetlands with no area changes. Climate change caused variations in wetland SOC density, and a future warming and drying climate would lead to decreases in wetland SOC storage. Estimates under Shared Socioeconomic Pathway 1‐2.6 (low‐carbon emissions) suggested that wetland SOC storage in China would not change significantly by 2100, but under Shared Socioeconomic Pathway 5‐8.5 (high‐carbon emissions), it would decrease significantly by approximately 5.77%. In this study, estimates of wetland SOC storage were optimized from three aspects, including sample database, wetland extent, and estimation method. Our study indicates the importance of using consistent SOC density and extent data in estimating and projecting wetland SOC storage.

The Influence of Geological Conditions in the Hangzhou Bay Area on the Deformation Behavior of Deep Excavations - Yihong Zhu; Mingming Wu; Gangping Zhang; Jianlin Yu; Qiliang Xu; Riqing Xu; Tianci Yu (Journal of Marine Science and Engineering, 2023)
The deformation behavior of deep excavations is affected by many factors, among which the geological conditions are greatly affected. Hangzhou Bay is affected by marine siltation and river alluvium, and the geological conditions within the urban area of Hangzhou are quite different. In this paper, the geological and deformation data of 79 deep excavation cases in the Hangzhou urban area were collected, and the statistical analysis showed that the deformation control of excavations in the silt area was poor. The average maximum lateral wall displacement of deep excavations of the Hangzhou urban area was 0.41%H (H was the depth of the excavation), the average value of the alluvial area was 0.22%H, and the average value of the silted area was 0.55%H. The influence of geological conditions, wall type, and construction period on the deformation of excavations was compared, and the deformation behavior of excavations in the silted area was clearly affected by various factors.

Dynamic prediction of SO2 emission based on hybrid modeling method for coal-fired circulating fluidized bed - Jiyu Chen; Mingming Gao; Hongfu Zhang; Haoyang Yu; Guangxi Yue (Fuel, 2023)

Influence pathways of nanocrystalline cellulose on the digestibility of corn starch: Gelatinization, structural properties, and α-amylase activity perspective - Huajian Xu; Zongwei Hao; Jinglei Zhang; Huixia Liu; Changyue Deng; Zhenyu Yu; Mingming Zheng; Yingnan Liu; Yibin Zhou; Yaqing Xiao (Carbohydrate Polymers, 2023)

Global depth distribution of belowground net primary productivity and its drivers - Liujun Xiao; Guocheng Wang; Jinfeng Chang; Yaoyao Chen; Xiaowei Guo; Xiali Mao; Mingming Wang; Shuai Zhang; Zhou Shi; Yiqi Luo; Lei Cheng; Kailiang Yu; et al. (Global Ecology and Biogeography, 2023)
Aim This study aimed to infer the allocation of belowground net primary productivity (BNPP) to sequential soil depths down to 2 m across the globe at a 1 km resolution and assess underlying environmental drivers. Location Global. Time Period Contemporary (1932–2017). Major Taxa Studied Terrestrial plants. Methods Global datasets including field net primary production (NPP, i.e., the difference between plant assimilated and respired carbon) from 725 soil profiles, root biomass and its depth distribution from 559 soil profiles were compiled and used to infer the depth distribution of BNPP across the globe and digitally map depth‐resolved BNPP globally at 1 km resolution. Drivers of the depth distribution of BNPP were evaluated using machine learning‐based models. Results Global average BNPP allocated to the 0–20 cm soil layer is estimated to be 1.1 Mg C ha −1 yr −1 , accounting for ~60% of total BNPP. Across the globe, the depth distribution of BNPP varies largely, and more BNPP is allocated to deeper layers in hotter and drier regions. Edaphic, climatic and topographic properties (in order of importance) explain >80% of such variability; and the direction and magnitude of the influence of individual properties are soil depth‐ and biome‐dependent. Main Conclusions The findings suggest that mean annual temperature and precipitation are the two most important factors regulating BNPP across the globe. Soil properties such as soil actual evaporation and total nitrogen also play a vital role in regulating the depth distribution of BNPP. The maps of BNPP provide global benchmarks of depth‐resolved BNPP for the prediction of whole‐profile soil carbon dynamics across biomes.

Investigation of underlying links between nitrogen transformation and microorganisms' network modularity in the novel static aerobic composting of dairy manure by “stepwise verification interaction analysis” - Yu Sun; Yonghui Xu; Jining Zhang; Ayodeji Bello; Xiang Li; Wanying Liu; Ugochi Uzoamaka Egbeagu; Liyan Zhao; Yue Han; Lijun Cheng; Wenhao Zhang; Qingxin Meng; et al. (Science of The Total Environment, 2023)

An interlayer flame retardant method to effectively fire retardant and reinforce CF/EP composites by nanofiber film intercalation - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Xueqiang Liu; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2023)

Water distribution and scheduling model of an irrigation canal system - Yu Fan; Haorui Chen; Zhanyi Gao; Yumiao Fan; Xiaomin Chang; Mingming Yang; Benyan Fang (Computers and Electronics in Agriculture, 2023)

The metabolism and dissipation behavior of tolfenpyrad in tea: A comprehensive risk assessment from field to cup - Zihan Wang; Fengjian Luo; Mingming Guo; Jiawei Yu; Li Zhou; Xinzhong Zhang; Hezhi Sun; Mei Yang; Zhengyun Lou; Zongmao Chen; Xinru Wang (Science of The Total Environment, 2023)

Neural spline flow multi-constraint NURBS method for three-dimensional automatic geological modeling with multiple constraints - Mingming Lyu; Bingyu Ren; Xiaoling Wang; Jiajun Wang; Jia Yu; Shuyang Han (Computational Geosciences, 2023)

Influence mechanism of wheat bran cellulose and cellulose nanocrystals on the storage stability of soy protein isolate films: Conformation modification and molecular interaction perspective - Yaqing Xiao; Huajian Xu; Qianxin Zhou; Weixiao Li; Junwei Gao; Xiangxin Liao; Zhenyu Yu; Mingming Zheng; Yibin Zhou; Xiaonan Sui; Yingnan Liu (Food Hydrocolloids, 2023)

Rapid along-strike variations of shallow crustal structure in response to Indo-Burma subduction: Constraints from multi-type passive seismic data - Yiming Bai; Jiayuan Yao; Shucheng Wu; Shengji Wei; Yu Wang; Stéphane Rondenay; Yumei He; Yinshuang Ai; Ping Tong; Mingming Jiang (Earth and Planetary Science Letters, 2023)

Geochemical characteristics and behaviors of polycyclic aromatic hydrocarbons (PAHs) in soil, water, and sediment near a typical nonferrous smelter - Miao Li; Mingming Shi; Tianpeng Hu; Weijie Liu; Yao Mao; Yue Yu; Haikuo Yu; An Xu; Wencong Yang; Xinli Xing; Jiaquan Zhang; Shihua Qi (Journal of Soils and Sediments, 2023)

Bioavailability and regional transport of PM2.5 during heavy haze episode in typical coal city site of Fenwei Plain, China - Weijie Liu; Yue Yu; Miao Li; Haikuo Yu; Mingming Shi; Cheng Cheng; Tianpeng Hu; Yao Mao; Jiaquan Zhang; Lili Liang; Shihua Qi; Xinli Xing (Environmental Geochemistry and Health, 2023)

Sparse Gaussian processes for multi-step motion prediction of space tumbling objects - Min Yu; Jianjun Luo; Mingming Wang; Chuankai Liu; Jun Sun (Advances in Space Research, 2023)

Visible light-driven photocatalytic degradation of Microcystin-LR by Bi2WO6/Reduced graphene oxide heterojunctions: Mechanistic insight, DFT calculation and degradation pathways - Mingming Zhan; Yu Hong; Zhi Fang; Daping Qiu (Chemosphere, 2023)

Trenchless rehabilitation of sewage pipelines from the perspective of the whole technology chain: A state-of-the-art review - Bin Li; Wei Yu; Yongen Xie; Hongyuan Fang; Xueming Du; Niannian Wang; Kejie Zhai; Dianchang Wang; Xianming Chen; Mingrui Du; Mingming Sun; Xiaohua Zhao (Tunnelling and Underground Space Technology, 2023)

Indoor air particles in research vessel from Shanghai to Antarctic: Characteristics, influencing factors, and potential controlling pathway - Xudong Wu; Fange Yue; Jiancheng Wang; Xiawei Yu; Hongwei Liu; Weihua Gu; Mingming Han; Juan Li; Zhouqing Xie (Journal of Environmental Sciences, 2023)

A model description of beta oscillations in the external globus pallidus - Mingming Chen; Yajie Zhu; Rui Zhang; Renping Yu; Yuxia Hu; Hong Wan; Dezhong Yao; Daqing Guo (Cognitive Neurodynamics, 2023)

On method of regional non-stationary flood frequency analysis under the influence of large reservoir group and climate change - Hao Cui; Shanhu Jiang; Bin Gao; Liliang Ren; Weihua Xiao; Menghao Wang; Mingming Ren; Chong-Yu Xu (Journal of Hydrology, 2023)

Residue behavior and risk assessment of afidopyropen and its metabolite M440I007 in tea - Mingming Guo; Hezhi Sun; Xinru Wang; Jiawei Yu; Fengjian Luo; Xinzhong Zhang; Mei Yang; Zhaoqun Li; Zongmao Chen; Li Zhou (Food Chemistry, 2023)

Human functional genomics reveals toxicological mechanism underlying genotoxicants-induced inflammatory responses under low doses exposure - Mingming Tian; Pu Xia; Lu Yan; Xiao Gou; Hongxia Yu; Xiaowei Zhang (Chemosphere, 2023)

Sodium alginate-based composite microspheres for controlled release of pesticides and reduction of adverse effects of copper in agricultural soils - Yu Du; Qizhen Zhang; Manli Yu; Bin Jiao; Fuliang Chen; Mingming Yin (Chemosphere, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

Formation of melanoidins and development of characterization techniques during thermal pretreatment of organic solid waste: A critical review - Mingming Yang; Lu Ding; Peiyao Wang; Yufan Wu; Chinnathan Areeprasert; Ming Wang; Xueli Chen; Fuchen Wang; Guangsuo Yu (Fuel, 2023)

Rotational strip intercropping of maize and peanut enhances productivity by improving crop photosynthetic production and optimizing soil nutrients and bacterial communities - Xiaoxia Zou; Yan Liu; Mingming Huang; Feng Li; Tong Si; Yuefu Wang; Xiaona Yu; Xiaojun Zhang; Haixin Wang; Puxiang Shi (Field Crops Research, 2023)

A field incubation approach to evaluate the depth dependence of soil biogeochemical responses to climate change - Xiaowei Guo; Xiali Mao; Wu Yu; Liujun Xiao; Mingming Wang; Shuai Zhang; Jinyang Zheng; Hangxin Zhou; Lun Luo; Jinfeng Chang; Zhou Shi; Zhongkui Luo (Global Change Biology, 2023)
Soil biogeochemical processes may present depth‐dependent responses to climate change, due to vertical environmental gradients (e.g., thermal and moisture regimes, and the quantity and quality of soil organic matter) along soil profile. However, it is a grand challenge to distinguish such depth dependence under field conditions. Here we present an innovative, cost‐effective and simple approach of field incubation of intact soil cores to explore such depth dependence. The approach adopts field incubation of two sets of intact soil cores: one incubated right‐side up (i.e., non‐inverted), and another upside down (i.e., inverted). This inversion keeps soil intact but changes the depth of the soil layer of same depth origin. Combining reciprocal translocation experiments to generate natural climate shift, we applied this incubation approach along a 2200 m elevational mountainous transect in southeast Tibetan Plateau. We measured soil respiration ( Rs ) from non‐inverted and inverted cores of 1 m deep, respectively, which were exchanged among and incubated at different elevations. The results indicated that Rs responds significantly ( p Rs from both non‐inverted and inverted cores become more sensitive to climate shifts, indicating higher vulnerability of persistent soil organic matter (SOM) to climate change than labile components, if labile substrates are assumed to be depleted with the proceeding of incubation. These results show in situ evidence that whole‐profile SOM mineralization is sensitive to climate change regardless of the depth location. Together with measurements of vertical physiochemical conditions, the inversion experiment can serve as an experimental platform to elucidate the depth dependence of the response of soil biogeochemical processes to climate change.

The community assembly for understanding the viral-assisted response of bacterial community to Cr-contamination in soils - Shuyue Liu; Yu Shi; Mingming Sun; Dan Huang; Wensheng Shu; Mao Ye (Journal of Hazardous Materials, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Analysis of micro-particle effect and methanogenic potential of food waste model compounds by hydrothermal pretreatment - Lu Ding; Mingming Yang; Chinnathan Areeprasert; Xiaopeng Cheng; Xueli Chen; Fuchen Wang; Guangsuo Yu (Fuel, 2023)

Effectiveness and degradation pathways of bisphenol A (BPA) initiated by hydroxyl radicals and sulfate radicals in water: Initial reaction sites based on DFT prediction - Qi Han; Mingming Wang; Feiyun Sun; Boping Yu; Zijun Dong; Pu Li; Jingwen Luo; Mu Li; Xingliang Jin; Zhiguang Dai (Environmental Research, 2023)

SCL, Encoding a Chloroplast Signal Recognition Particle Receptor, Affects Chlorophyll Synthesis and Chloroplast Development in Rice - Jing Ye; Shenghai Ye; Rongrong Zhai; Mingming Wu; Faming Yu; Guofu Zhu; Xiaoming Zhang (Journal of Plant Growth Regulation, 2023)
Crop yield is largely determined by the solar energy utilization efficiency of photosynthesis; plants with long stay-green periods have greater total photosynthetic production levels and crop yields. Here, a novel seedling chlorosis and lethality ( scl ) mutant exhibiting a yellow leaf and seedling-lethal phenotype was identified in rice ( Oryza sativa L.). The mutant had deformed chloroplasts and almost no protein complexes in thylakoid membranes. The expression levels of photosynthesis-associated genes were significantly down-regulated in scl compared with the wild-type (WT). Positive transgenic lines generated by Agrobacterium tumefaciens -mediated transformation of the scl mutant with a complementation vector harboring SCL cDNA exhibited the normal green leaf phenotype, whereas the scl seedling harboring the empty vector displayed the yellow leaf phenotype, indicating that SCL is LOC_Os01g72800. A fusion protein expressing SCL with green fluorescent protein revealed the fluorescence signal localized to chloroplasts. The expression patterns of chloroplast development and chlorophyll biosynthesis and degradation-related genes were disordered in scl mutant, possibly resulting in the yellow leaf phenotype. These results indicated that the SCL loss of function impaired chloroplast development, chlorophyll biosynthesis, and light-harvesting chlorophyll-binding protein transportation in rice.

Influence of temperature and precipitation on the fate of polycyclic aromatic hydrocarbons: simulation experiments on peat cores from a typical alpine peatland in Central China - Haikuo Yu; Tianpeng Hu; Yao Mao; Ting Liao; Mingming Shi; Weijie Liu; Miao Li; Yue Yu; Yuan Zhang; Xinli Xing; Shihua Qi (Environmental Science and Pollution Research, 2022)

The growth and lipid accumulation of Scenedesmus quadricauda under nitrogen starvation stress during xylose mixotrophic/heterotrophic cultivation - Yiwen Mou; Na Liu; Kunyang Su; Xue Li; Tianxiang Lu; Ze Yu; Mingming Song (Environmental Science and Pollution Research, 2022)

Beta-Boswellic Acid Protects Against Cerebral Ischemia/Reperfusion Injury via the Protein Kinase C Epsilon/Nuclear Factor Erythroid 2-like 2/Heme Oxygenase-1 Pathway - Mingming Wang; Jiaoyan Yu; Qi Yang; Chao Guo; Wei Zhang; Weiwei Li; Yan Weng; Yi Ding; Jingwen Wang (Molecular Neurobiology, 2022)

Evaluation of Chito-Oligosaccharide (COS) in Vitro and in Vivo: Permeability Characterization in Caco-2 Cells Monolayer and Pharmacokinetics Properties in Rats - Pengpeng Zhang; Miaomiao Zhang; Kaiyu Dong; Yicong Zhang; Shuang Yang; Yuanhong Wang; Tingfu Jiang; Mingming Yu; Zhihua Lv (Journal of Ocean University of China, 2022)

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Functional metabolome profiling may improve individual outcomes in colorectal cancer management implementing concepts of predictive, preventive, and personalized medical approach - Yu Yuan; Chenxin Yang; Yingzhi Wang; Mingming Sun; Chenghao Bi; Sitong Sun; Guijiang Sun; Jingpeng Hao; Lingling Li; Changliang Shan; Shuai Zhang; Yubo Li (EPMA Journal, 2022)

Rapid visual detection of Aeromonas salmonicida by loop‐mediated isothermal amplification with hydroxynaphthol blue dye - Shun Zhou; Qing Huang; Mingming Yu; Ying Li; Xujia Zheng; Yunji Xiu (Journal of Fish Diseases, 2021)
To make crucial prevention, reduce fish losses and minimize the economic damage of diseases on the fish farm owners, a rapid detection of fish pathogens is mandatory. In this study, a loop‐mediated isothermal amplification assay combined with hydroxynaphthol blue dye (LAMP‐HNB) was developed and used for the rapid detection of Aeromonas salmonicida that caused significant economic losses in fish farming. Firstly, a pair of outer and inner primers specific for conserved fragment of vapA gene in A. salmonicida were designed and synthesized. Secondly, by optimizing the reaction conditions including reaction temperature, time, Mg 2+ concentration, dNTP concentration and primer ratio, a LAMP‐HNB assay was successfully established for the detection of A. salmoncida . Thirdly, the assay showed good specificity with no false‐positive and false‐negative results, and good sensitivity with the detection limit of 3.077 × 10 –6 ng/μl, which was 10 2 times more sensitive than the conventional PCR. Finally, the LAMP‐HNB assay was validated by the fish samples inoculated with different concentrations of A. salmoncida . This is the first development of rapid visual detection of A. salmonicida based on LAMP‐HNB assay, which has great application prospect and market for diagnostic testing, health certification and active surveillance programmers.

Icariin enhance mild hypothermia-induced neuroprotection via inhibiting the activation of NF-κB in experimental ischemic stroke - Mingming Dai; Bin Chen; Xiaozhi Wang; Chang Gao; Hang Yu (Metabolic Brain Disease, 2021)

Colorimetric and Ratiometric Fluorescence Detection of HSO3− With a NIR Fluorescent Dye - Wenjie Liu; Chenchen Yang; Hongyan Zhang; Zhanxian Li; Mingming Yu (Journal of Fluorescence, 2021)

Independent and combined associations of solid-fuel use and smoking with obesity among rural Chinese adults - Mingming Pan; Jianjun Gu; Ruiying Li; Hao Chen; Xiaotian Liu; Runqi Tu; Ruoling Chen; Songcheng Yu; Zhenxing Mao; Wenqian Huo; Jian Hou; Chongjian Wang (Environmental Science and Pollution Research, 2021)

Preparation of Yellow Fluorescent N,O-CDs and its Application in Detection of ClO− - Qiang Zhang; Huanhuan Song; Mingming Yu; Hongyan Zhang; Zhanxian Li (Journal of Fluorescence, 2021)

Bearing capacity behaviour of prestressed anchor cable under slope blasting excavation - Guofeng Li; Ning Li; Chong Yu; Mingming He (Arabian Journal of Geosciences, 2021)

Association between selected urinary heavy metals and asthma in adults: a retrospective cross-sectional study of the US National Health and Nutrition Examination Survey - Xiuzhu Li; Yun Fan; Yan Zhang; Xiaomin Huang; Zhenyao Huang; Mingming Yu; Qiaoqiao Xu; Xiumei Han; Chuncheng Lu; Xinru Wang (Environmental Science and Pollution Research, 2021)

Sphagnum spore banks in two montane peatlands at different elevations - Ling-Zhi Wang; Lu Feng; Zhao-Jun Bu; Sebastian Sundberg; Mingming Zhang; Xu Chen; Yun-He Yang; Xiao-Ya Yu; Wen-Jing Liu (Wetlands Ecology and Management, 2020)

Simultaneous Quantification of κ-Carrageenan Oligosaccharides of DP 3, 5 and 7 by LC-MS/MS: Application to an in vitro Absorption Study - Yali Yang; Pengpeng Zhang; Guilin Liu; Shuang Yang; Yuanhong Wang; Tingfu Jiang; Zhihua Lv; Mingming Yu (Journal of Ocean University of China, 2020)

1H NMR Quantification of DHA and EPA in Fish Oil - Jinxiao Lv; Cong Wang; Xiuli Zhang; Zhihua Lv; Mingming Yu (Journal of Ocean University of China, 2020)

MiR-146b protects against the inflammation injury in pediatric pneumonia through MyD88/NF-κB signaling pathway - Lei Zhang; Lili Dong; Yu Tang; Min Li; Mingming Zhang (Infectious Diseases, 2020)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Simulating and assessing the evolution of collapsing gullies based on cellular automata-Markov and landscape pattern metrics: a case study in Southern China - Xiang Ji; Anita Thompson; Jinshi Lin; Fangshi Jiang; Shaoxin Li; Mingming Yu; Yanhe Huang (Journal of Soils and Sediments, 2019)

Identification of a major QTL affecting resistance to brown spot in tobacco (Nicotiana tabacum L.) via linkage and association mapping methods - Mingming Sun; Lirui Cheng; Caihong Jiang; Chengguang Zhu; Min Ren; Yusheng Zhang; Yu Zhang; Dan Liu; Qiang Zhao; Ruimei Geng; Xiaoli Hu; Aiguo Yang; et al. (Euphytica, 2018)

Evaluation of the protective effect of a prime-boost strategy with plasmid DNA followed by recombinant adenovirus expressing BmAMA1 as vaccines against Babesia microti infection in hamster - Guanbo Wang; Longzheng Yu; Artemis Efstratiou; Paul Franck Adjou Moumouni; Mingming Liu; Huanping Guo; Yang Gao; Shinuo Cao; Mo Zhou; Jixu Li; Aaron Edmond Ringo; Xuenan Xuan (Acta Parasitologica, 2018)
In the present study, we have investigated the protective effect of a heterologous prime-boost strategy with priming plasmid DNA followed by recombinant adenovirus, both expressing BmAMA1, against Babesia microti infection. Four groups consisting of 3 hamsters per group were immunized with pBmAMA1/Ad5BmAMA1, pNull/Ad5BmAMA1, pBmAMA1/Ad5Null and pNull/Ad5Null, followed by challenge infection with B . microti . Our results showed that hamsters immunized with plasmid and adenovirus expressing BmAMA1 developed a robust IgG and IgG2a antibody response against BmAMA1, suggesting the DNA vaccine or viral vector vaccine tend to induce a Th1-biased response. Compared to the control hamsters, the hamsters vaccinated either with the prime-boost strategy or one of the two “vaccines” exhibited no significant protection against B . microti challenge. Although a slight difference in terms of parasitemia and hematocrit values at days 14–16 post challenge infection was observed, no other statistical difference was detected. Our results indicate that the prime-boost vaccination strategy of injection of plasmid and adenovirus expressing BmAMA1 is not efficient in protecting against B . microti infection.

Acquiring high-resolution topography and performing spatial analysis of loess landslides by using low-cost UAVs - Sheng Hu; Haijun Qiu; Xingang Wang; Yu Gao; Ninglian Wang; Jiang Wu; Dongdong Yang; Mingming Cao (Landslides, 2018)

Annexin A2 Plus Low-Dose Tissue Plasminogen Activator Combination Attenuates Cerebrovascular Dysfunction After Focal Embolic Stroke of Rats - Xiang Fan; Yinghua Jiang; Zhanyang Yu; Qi Liu; Shuzhen Guo; Xiaochuan Sun; Klaus van Leyen; MingMing Ning; Xiumei Gao; Eng H. Lo; Xiaoying Wang (Translational Stroke Research, 2017)

Comparative study on magnetic minerals of tidal flat deposits from different sediment sources in Jiangsu coast, Eastern China - Longsheng Wang; Shouyun Hu; Ge Yu; Mingming Ma; Mengna Liao (Studia Geophysica et Geodaetica, 2017)

Evaluation of the applicability of climate forecast system reanalysis weather data for hydrologic simulation: A case study in the Bahe River Basin of the Qinling Mountains, China - Sheng Hu; Haijun Qiu; Dongdong Yang; Mingming Cao; Jinxi Song; Jiang Wu; Chenlu Huang; Yu Gao (Journal of Geographical Sciences, 2017)

A new parameter as an indicator of the degree of deformation of coals - Mingming Wei; Yiwen Ju; Quanlin Hou; Guochang Wang; Liye Yu; Wenjing Zhang; Xiaoshi Li (Journal of Earth Science, 2017)

Telomere length is regulated by FGF-2 in human embryonic stem cells and affects the life span of its differentiated progenies - Yu Zou; Huei Jinn Tong; Mingming Li; Kai Soo Tan; Tong Cao (Biogerontology, 2017)

High-level expression and biochemical characterization of a novel cold-active lipase from Rhizomucor endophyticus - Xiaojie Duan; Mingming Zheng; Yu Liu; Zhengqiang Jiang; Shaoqing Yang (Biotechnology Letters, 2016)

Expression, purification and characterization of a vascular endothelial growth factor fusion protein - Yu Zhang; Yue Tong; Mingming Gao; Cheng Luo; Xiaoda Song; Xiangdong Gao; Wenbing Yao (Biotechnology Letters, 2016)

Feasibility of an enhanced washing process to extract PBDEs/heavy metals/antibiotics from antibiotic resistance gene-affected soil with aqueous DNA followed by microbial augmentation - Mao Ye; Mingming Sun; Jinzhong Wan; Yu Zhao; Shanni Xie; Da Tian; Feng Hu; Huixin Li; Lianggang Zong; Fredrick Orori Kengara; Jiang Xin (Journal of Soils and Sediments, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The influence of three mangrove species on the distribution of inorganic nitrogen and phosphorus in the Quanzhou Bay estuarine wetland soils - Guiyao Zhou; Yanyou Wu; Deke Xing; Mingming Zhang; Rui Yu; Weiyi Qiao; Qaiser Javed (Acta Geochimica, 2016)

Myo10 is required for neurogenic cell adhesion and migration - Huali Yu; Mingming Lai; Yuguang Guo; Lin Yuan; Yongsheng Lan; Xingzhi Wang; Xiaojuan Zhu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Stereoselective degradation of flutriafol and tebuconazole in grape - Qing Zhang; Xiude Hua; Yu Yang; Wei Yin; Mingming Tian; Haiyan Shi; Minghua Wang (Environmental Science and Pollution Research, 2015)

Remote Detection of Shoreline Changes in Eastern Bank of Laizhou Bay, North China - Yuandong Wang; Xiyong Hou; Mingming Jia; Ping Shi; Liangju Yu (Journal of the Indian Society of Remote Sensing, 2014)

Effects of sulfate chitosan derivatives on nonalcoholic fatty liver disease - Mingming Yu; Yuanhong Wang; Tingfu Jiang; Zhihua Lv (Journal of Ocean University of China, 2014)

Association between polymorphisms in the promoter region of interleukin-10 and susceptibility to inflammatory bowel disease - Hongchao Lv; Yongshuai Jiang; Jin Li; Mingming Zhang; Zhenwei Shang; Jiajia Zheng; Xin Wu; Panpan Liu; Ruijie Zhang; Huimin Yu (Molecular Biology Reports, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)